Oil price and the development of financial intermediation in developing oil-exporting countries: Evidence from Nigeria - Chinazaekpere Nwani; Eugene Iheanacho; Chijioke Okogbue (Cogent Economics & Finance, 2016)
This study examines the relationship between crude oil price and financial sector intermediary development in Nigeria over the period 1975-2011, using the autoregressive distributed lag approach to cointegration analysis. Four measures of financial intermediary development are used including an index of financial intermediary development constructed from three indicators of financial intermediary development using principal component analysis. The results show that crude oil price is a key driver of financial intermediary development in Nigeria. A positive and significant long run relationship between financial intermediary development and crude oil price coexists with a negative short run relationship. The results show that even if we control for economic growth, inflation and trade openness, crude oil price still has significant influence on the development of financial intermediation in Nigeria. The findings of this study have important policy implications for financial intermediary development in Nigeria and other developing oil-exporting countries.
Keywords: G20; O11; Q32; 330; financial development; oil price; macroeconomic performance; oil-exporting countries; Nigeria; ARDL